THE CONCEPT OF CORPORATE SOCIALRESPONSIBILITY IN SHARIA BANKING BASED ON SHARIA ENTERPRISE THEORY: LITERATURE REVIEW STUDY - Suryani, Yani (Proceeding International Seminar of Islamic Studies, 2023)
The implementation of sharia-based social responsibility in Islamic banking is one form of the role/responsibility of human beings as caliphs on earth towards Allah SWT, fellow humans and nature. So it is also important to study the concept of CSR based on SET/Shariah Enterprise Theory in Islamic Banking. Several stages in the presentation of the concept of Corporate Social Responsibility in Islamic Banking include collecting references on the concept of CSR based on SET. Next, select sources and conduct an in-depth study of the references that have been selected, as well as make discussions and conclusions. The results of the study show that the concept of Corporate Social Responsibility in Islamic Banking is based on SET (Shariah Enterprise Theory) which provides an explanation that there are themes and elements that must be disclosed in reporting social responsibility in Islamic Banking. Reporting implementation that must be disclosed in CSR Disclosure based on sharia Enterprise Theory (SET) in the sharia banking sector includes two dimensions, namely vertical and horizontal accountability. Fulfillment of responsibility vertically to Allah SWT as the primary trustee. Horizontal accountability: direct stakeholders (customers and employees), Horizontal accountability: indirect stakeholders (society and nature).